IMPLEMENTATION OF CHAIN STORY TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING SKILLS IN THE THIRD GRADE OF SDN 136 PEKANBARU - Nurhalimah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research was conducted to improve students’ speaking skills in the third grade of SDN 136 Pekanbaru. This research was conducted due to the low speaking skill of the students. The chain story technique was applied to improve the speaking skills of the third grade students of SDN 136 Pekanbaru. Chain story technique is one of the techniques for teaching speaking that tells a story to the first student then continue to the second student, and at last the story is being told to the first student. This technique was expected to improve students' speaking skills with the correct pronunciation, loud voice, coherent sentences, and fluency. The type of the research was classroom action research with 27 students as the subjects, 17 females and 10 males. The study was conducted in October. The data were obtained through performance tests. After applying the chain story technique, teacher’s activity had increased in the first cycle from 60% to 65% and the second cycle was from 70% to 85%. Furthermore, the students’ activity had also increased in the first cycle from 60% to 70% and the second cycle from 75% to 85%. The improvement of students’ speaking skills in the third grade of SDN 136 Pekanbaru could be seen from the increasing of the average value of the first cycle (66.04) to the second cycle (77.46) with the percentage of the first cycle was 6.04% and increased to the second cycle with 20.97%. Thus, it can be concluded that the implementation of the chain story technique can improve the students’ speaking skills of the third grade of SDN 136 Pekanbaru.